Effect of Experimental Pain and Visual Feedback on the Accuracy and Precision of Knee Joint Position Sense - Shaojun Liao; Lars Arendt-Nielsen; Kelun Wang; Rogerio Pessoto Hirata (Pain Research and Management)
Trial Registration: ClinicalTrials.gov identifier: NCT04146311